What do we know about the future of land in relation to food systems? - Robertson, Richard D.; Cenacchi, Nicola; Mishra, Abhijeet (International Food Policy Research Institute, 2025)
The total amount of cropland across the globe is likely to expand over the next three decades due to rising demand for food along with feed for livestock.